Representation of a Standard Continuous Function by a Microscope - Tahir Ismail; Hind Saleh (Al-Rafidain Journal of Computer Sciences and Mathematics)
The aim of this paper is to provide a representation of a standard continuous function and a standard differentiable function by mean of a microscope. More precisely, under certain conditions, the following results have been obtained.